2011
DOI: 10.1210/en.2011-1286
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Engagement Protects Human β-Cells from Apoptosis

Abstract: The aim of this study was to assess the expression of different types of cadherins in human islets and their role in human β-cell apoptosis. Expression of E-, N-, and P-cadherins was studied by immunofluorescence on pancreas sections and islet cells, and by Western blotting on protein extracts of isolated islets and islet cells. The effects of specific cadherins on cell adhesion and apoptosis were studied using chimeric proteins containing functional E-, N-, or P-cadherin ectodomains fused to Fc fragment of Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
3
33
1
Order By: Relevance
“…As expected from our previous study (21), Western blotting showed that expressions of N-and E-cadherins were low immediately after Accutase treatment and time-dependently increased after incubation ( Fig. 1).…”
Section: Cadherin Expression In Islet Cells Is Not Affected By Glucosesupporting
confidence: 89%
See 3 more Smart Citations
“…As expected from our previous study (21), Western blotting showed that expressions of N-and E-cadherins were low immediately after Accutase treatment and time-dependently increased after incubation ( Fig. 1).…”
Section: Cadherin Expression In Islet Cells Is Not Affected By Glucosesupporting
confidence: 89%
“…Under the studied conditions, E-cad/Fc had more effect that N-cad/Fc in increasing glucoseinduced insulin secretion. The same difference was previously observed when similar experiments were conducted to assess the effect of cadherin engagement on apoptosis of b-cells (21). The reason for the differential effects of N-and E-cadherins is not yet understood.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Secondary wave endocrine cells primarily differentiate into -cells, along with other endocrine lineages, delaminate from the epithelium and coalesce into small islet-like clusters that progressively form larger islet aggregates during postnatal development. Cell-cell interactions both between -cells, and between -cells and ECs are important for islet development and insulin secretion (Nikolova et al, 2006;Parnaud et al, 2011). Interactions between -cells within islets, occurring via EphA-ephrin A signaling, were shown to reduce insulin secretion under conditions of low glucose and to enhance secretion when blood glucose levels increased (Konstantinova et al, 2007).…”
Section: Ontogeny Of the -Cellmentioning
confidence: 99%